2014
DOI: 10.3748/wjg.v20.i24.7894
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation, microRNAs, and their crosstalk as potential biomarkers in hepatocellular carcinoma

Abstract: Epigenetic alterations have been identified as a major characteristic in human cancers. Advances in the field of epigenetics have contributed significantly in refining our knowledge of molecular mechanisms underlying malignant transformation. DNA methylation and microRNA expression are epigenetic mechanisms that are widely altered in human cancers including hepatocellular carcinoma (HCC), the third leading cause of cancer related mortality worldwide. Both DNA methylation and microRNA expression patterns are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 235 publications
2
67
0
Order By: Relevance
“…Their aberrant expression is associated with various malignant tumors including HCC [32]. So far, downregulation of miR-let-7g, -22, -26, -29, -99a, -122, -124, -139, -145, -199b, and -185 acting as tumor suppressor genes and upregulation of miR-10b, -17-5p, -21, -135a, -155, -182, -221, and -222 acting as candidate oncogenes have already been observed in HCC [13].…”
Section: Discussionmentioning
confidence: 99%
“…Their aberrant expression is associated with various malignant tumors including HCC [32]. So far, downregulation of miR-let-7g, -22, -26, -29, -99a, -122, -124, -139, -145, -199b, and -185 acting as tumor suppressor genes and upregulation of miR-10b, -17-5p, -21, -135a, -155, -182, -221, and -222 acting as candidate oncogenes have already been observed in HCC [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one-carbon metabolism in the nucleus plays a critical role in DNA replication and repair and in DNA methylation, a regulatory epigenetic process [19]. A simple abnormality in the methylation pathway, compounded with further assaults from environmental and infectious agents can lead to a wide range of conditions including, for example, cardiovascular disease, neurotransmitter imbalances, cancer, diabetes, abnormal immune function, and chronic inflammation.…”
Section: Roles Of Betaine In Mammalsmentioning
confidence: 99%
“…Despite the unclear molecular pathogenesis of HCC, it has been confirmed that epigenetic aberrance, especially DNA methylation, plays an important role in the progression of carcinoma (Chen et al, 2013;Anwar and Lehmann, 2014;Dong and Wang, 2014). The silence of many tumor suppressor genes (TSGs), caused by the aberrant CpG island methylation of gene promoter, is considered as an early event for HCC pathogenesis (Chang et al, 2008;Nishida et al, 2008;Moribe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%